(untitled) (New York, 1991)
Presents case studies of how North American, Asian, and Oceanic governments have intervened to help ailing industries, and the impact their actions have had on the industry, the country's economy, and the growth of free trade. The primary goal is to find alternatives to knee-jerk import controls.
Keywords: Industries,Pacific Area,Công nghiệp,Khu vực Thái Bình Dương; Case studies,Congresses,Foreign economic relations,Case studies,Congresses,Nghiên cứu trường hợp,Hội nghị,Quan hệ kinh tế đối ngoại,Nghiên cứu trường hợp,Hội nghị; Pacific Area,Khu vực Thái Bình Dương